THE EFFECT OF TRAINING USING SLOW-MOTION VIDEO ON CORRECTING THE SKILL PERFORMANCE OF THE LONG SERVE IN TABLE TENNIS - Hamdullah Abed Hammadi (Proximus Journal Publishing, 2026)
This research aims to examine the impact of slow-motion video training on correcting the technical performance of long serves in table tennis among junior players. The study relies on employing slow-motion replay as an instructional tool that enables players to observe subtle execution errors and work on correcting them. The researcher adopted the experimental method with two groups: an experimental group trained using slow-motion video analysis, and a control group trained using traditional methods. The sample consisted of 20 randomly selected junior players, equally distributed between the two groups. A training program was implemented over four weeks, with three sessions per week, involving practical exercises captured on video and immediate feedback from the coach for each player. Technical performance of the long serve was assessed before and after the program using skill-based evaluation tools and motion analysis software. The results revealed statistically significant differences in favor of the experimental group in the post-test. These findings confirm the effectiveness of slow-motion video in improving technical skills. The study recommends integrating this technique into training programs, especially for early age categories.
Keywords: Table Tennis; Slow-Motion Video; Technical Performance